2022
DOI: 10.1177/09697330221122904
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the concept of non-violent resistance amongst healthcare workers

Abstract: Background Non-violent resistance which has involved healthcare workers has been instrumental in securing a number of health-related gains and a force in opposing threats to health. Despite this, we know little about healthcare workers who have engaged in acts of non-violent resistance. Research aim Amongst a sample of healthcare workers who had engaged in acts of resistance this study sought to explore their understanding of non-violent resistance and how or whether they felt healthcare workers made a distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Traditional command‐and‐control leadership has shown less effectiveness than diverse team leadership that is supported by their respective organizations. Furthermore, hierarchical leadership structures limit the ability of “lower ranking” team members to voice opinions, make implementing change and innovation difficult, and contribute to gender and ethnic inequalities and discriminatory practices 99 . Diverse team leadership groups have demonstrated to be a characteristic of high‐performing teams, 100 with greater success in innovation and outcomes 101 .…”
Section: Discussionmentioning
confidence: 99%
“…Traditional command‐and‐control leadership has shown less effectiveness than diverse team leadership that is supported by their respective organizations. Furthermore, hierarchical leadership structures limit the ability of “lower ranking” team members to voice opinions, make implementing change and innovation difficult, and contribute to gender and ethnic inequalities and discriminatory practices 99 . Diverse team leadership groups have demonstrated to be a characteristic of high‐performing teams, 100 with greater success in innovation and outcomes 101 .…”
Section: Discussionmentioning
confidence: 99%
“…al. 2022 ). Participants were originally recruited through the Medact ( https://www.medact.org/ ) member database.…”
Section: Methodsmentioning
confidence: 99%
“…However, isn't a prayer and a Christian response to workplace mobbing a passive, losing strategy? Indeed, nonviolent resistance is not a new topic, but according to Ryan Essex et al (2023), such a response remains a disputed concept in regard to the forms and consequences of such resistance. Although nonviolent individual responses to violence are most often examined in the context of collective resistance (Dahlum et al 2022;Essex et al 2023;Vollhardt et al 2020), it is important to understand the motives that drive people to adopt these strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, nonviolent resistance is not a new topic, but according to Ryan Essex et al (2023), such a response remains a disputed concept in regard to the forms and consequences of such resistance. Although nonviolent individual responses to violence are most often examined in the context of collective resistance (Dahlum et al 2022;Essex et al 2023;Vollhardt et al 2020), it is important to understand the motives that drive people to adopt these strategies. For example, a study conducted by Ryan Essex et al ( 2023) demonstrated that 12.9% of physicians surveyed mentioned conscience, ethical, moral beliefs or principles.…”
Section: Introductionmentioning
confidence: 99%